PENGARUH MOTIVASI KERJA, KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA KARYAWAN POLITEKNIK NEGERI MEDIA KREATIF JAKARTA - Hesti Prasetiya Ningrum, (2021)
The purpose of this study was to determine the effect of work motivation, compensation and work environment on job satisfaction of the employees of the Jakarta Creative Media State Polytechnic. The data used is quantitative data with a population of 258 employees at Polimedia and a sample of 115 employees at Polimedia. This research hypothesis was tested using Multiple Linear Regression Analysis Method with SPSS software program and with a significant level of 5%. The results obtained from this study are (1) there is a significant influence between work motivation and job satisfaction, (2) there is a significant influence between compensation and job satisfaction, (3) there is a significant influence between work environment and job satisfaction, and (4) there is a significant influence between motivation, compensation and work environment simultaneously or together on job satisfaction.